Policy Analysis of Blok M Area Planning in Shaping Spatial Configuration and Area Effectiveness - Arina Marta Setya Putri; Rizal Imana (Journal of Synergy Landscape, 2026)
Blok M is one of Jakarta's important urban centers, serving not only as a commercial and service area but also as a major public transport interchange. Its development has been reinforced by Governor Regulation Number 55 of 2020 on the Urban Design Guidelines for the Blok M-Sisingamangaraja Transit-Oriented Development area. Official publications from PT MRT Jakarta indicate that the TOD area covers about 113.7 hectares, with priority development concentrated within a 700-meter radius of Blok M BCA Station and ASEAN Station. This study examines how area-planning policy in Blok M shapes spatial configuration and how that configuration affects area effectiveness. The study uses a descriptive qualitative approach based on policy analysis of regulations, institutional documents, and official publications issued by government agencies and area operators. The findings show that planning policy in Blok M has guided the integration of transit nodes, pedestrian connections, mixed-use development, and public-space improvement. These policy directions have contributed to better accessibility, stronger functional links between urban activities, smoother internal movement, and greater support for social and economic activity. In this case, planning policy works not only as a regulatory tool, but also as a framework that structures how spaces in the district are connected and used.